The Effect of Temperature on the Kinetics of the Structure Formation of a Carbonate-Gypsum Mixture Based on A Natural Gypsum Binder (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The article studies the influence of temperature on the kinetics of the structure formation of a carbonate-gypsum mixture and the features of the structure formation of various gypsum binders. Despite the formation of the same CaSO4∙2H2O phase during hydration of various low-temperature binders, they differ in strength and kinetics of its increase. The results of thermogravimetric analysis of hydration products of carbonate-gypsum binder are presented. The analysis of hydration products in kinetics confirms that the formation of a hardening structure in firing products up to 600оC is determined by the hydration of insoluble anhydrite and the crystallization of ultimately two-water gypsum, and as a result of high-temperature firing of carbonate-gypsum mixtures, it is possible to obtain a binder capable of hydraulic hardening.